Ischemia-modified albumin as a possible marker of oxidative stress in patients with telogen effluvium, - Unsal Savci; Engin Senel; Aynure Oztekin; Mustafa Sungur; Ozcan Erel; Salim Neselioglu (Sociedade Brasileira de Dermatologia, 2020)
Abstract Background Telogen effluvium is the most common form of non-scarring alopecia characterized by diffuse hair loss. Ischemia-modified albumin is a marker of oxidative stress and inflammation. Objective The aim of this study was to compare the levels of ischemia-modified albumin of telogen effluvium patients with healthy controls. Methods Ninety-one patients diagnosed with telogen effluvium and 35 healthy volunteers were included in the study. Serum ischemia-modified albumin level was determined by a fast-colorimetric method, and albumin cobalt binding test. The results were evaluated statistically. Results There was no statistically significant difference between the serum albumin values of patient and control groups (p = 0.739). Serum ischemia-modified albumin values were significantly higher in the patients with telogen effluvium than healthy controls (p < 0.001). Study limitations Body mass index values of the patient and control groups could not be calculated. Conclusions To the best of the authors' knowledge, this is the first clinical study to investigate the role of oxidative stress in the pathogenesis of telogen effluvium using ischemia-modified albumin as a biomarker. Based on the results of the present study, it can be considered that oxidative stress plays an important role in the pathogenesis of telogen effluvium. There is a need for further studies to support the results of this study, to demonstrate the possible effects of oxidative stress, and to investigate the other oxidative stress markers in the pathogenesis of telogen effluvium.